The Effect of Regional Financial Ratios, Regional Original Income, General Allocation Funds, and Special Allocation Funds on Capital Expenditures in North Sumatra Province Period (2018 – 2020) - Nina Purnasari; Hertina Ompusunggu; Saprianus Buulolo (Budapest International Research and Critics University, 2022)
The rationale behind this study is to decide whether the level of environmental finance, self-financing (PAD), publicly owned stores (DAU), and honors (DAK) affect capital expenditures. Specifically. This audit is being pushed. From 2018 to 2020, North Sumatra has 33 metropolitan areas and associations. It discusses the full population of the 33 closest associations and metropolitan areas in North Sumatra.l The information used in this general description is taken from the Regional Revenue and Expenditure Budget of North Sumatra through the website http://www.djpk.kemenkeu.go.id /entrance/information/apdh. Test Method Used Dental Assessment Dazzling TestOther Direct Variable Tests Bonding Dental Capital Output and Dental Opportunity Factors Nearest Asset Level, Regional Special Salaries (PAD), General Reserves (DAU), Special Allocation Funds (DAK) distributed. In this way, the level of financial independence in the domain slightly affects capital expenditures, but compensation from the top of the district, public transport resources, and extraordinary arrangements support fairly strong capital utilization to do it is shown.